Uji Daya Hambat Tepung Tanaman Kenikir (Cosmos caudatus kunth) terhadap Bakteri Salmonella Sp, Escherichia coli Serta Evaluasi Senyawa Zat Aktif Flavonoid, Polifenol dan Saponin - Maria Selfiana Pasi; Irfan H. Djunaidi; M. Halim Natsir (JAS, 2022)
This study aims to determine the extent to which parts of the kenikir plant have the inhibitory power of salmonella sp, escherichia coli bacteria and evaluate the active compounds of flavonoids, polyphenols and saponins that have the potential as feed additives. This research was carried out at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya and the Laboratory of Metria Medica Batu Malang on October 22, 2018. This study used an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 6 replications. Treatments P0 (bacterial isolate + Aquades 30 %), P1 (bacterial isolate + 30% kenikir leaf powder concentration solution), P2 (bacterial isolate + 30% kenikir stem flour concentration solution), P3 (bacterial isolate + Leaf and stem flour concentration solution cringe 30%). The parameters observed were the inhibition of kenikir flour plant parts against Salmonella sp., Escherichia coli bacteria and evaluation of the active compounds of flavonoids, polyphenols and saponins from kenikir plant flour. The results showed that the effect of differences in flour from the part of the kenikir plant on the inhibition of bacteria was very significant (P<0.01) on Salmonella sp and Escherichia coli bacteria.